Kaj Slovenci počnemo z ameriško poezijo? - Novak-Popov, Irena (Primerjalna književnost, 2019)
There is a growing interest for American poetry in Slovenia during the last four decades: we translate the classic poets, starting with W. Whitman and W. C. Williams, proceeding to W. Stevens, poets of the beat generation and New York school, and recently to younger, not-yet- canonized, where the translators are poets themselves and often also writers of introductory studies. Poets who in the 1990s redirected Slovene poetry towards postmodernism, loosening the dissident heritage of elitist modernism, appropriated and adapted to domestic literary context the subject's attitudes, poetic strategies, thematic and genre tendencies (openness, inclusion of popular culture, media and music, colloquial idiom, fragments of autobiographic narrative, urban setting) that had first been practiced in certain American poetry. My interest is focused primarily on friendly interconnected circle of Ljubljana poets and translators Tone Škrjanec, Primož Čučnik, Gregor Podlogar and Ana Pepelnik. Using intertextual theory instead of researching "influences", I analyze how they have responded to, assimilated and transformed the impulses form American poetry they read, translated, presented and got acquainted with by means of productive interpersonal contacts. Their film like dynamic imagery is made of subjectively perceived elements of urban reality, overflowing the speaker-observer, they assume ironic and critical attitude towards contemporary social phenomena, playfully experiment with language, insist on colloquial informality and cleverly adapt the transferred literary models to their own needs. The peculiarity of the Other is filtered through avant-garde procedures (collage-making), philosophy of indeterminacy, flowing of music, or even becomes material for remaking/recycling.
Keywords: ameriška poezija; Čučnik, Primož; književnost; literarni vplivi; medliterarni transfer; Pepelnik, Ana; Podlogar, Gregor; prevajanje; prevodi v slovenščino; sodobna slovenska poezija; Škrjanec, Tone